Effects of roller chooping and buffelgrass seeding on grass evolution in a degraded shrubland of arid Chaco region (Semiárida, 2020)
In Argentinean Chaco Arid region, rolling and buffelgrass seeding is widespread. In this region, information related to its short and medium time effects on vegetation attributes is available. The purpose of this study was to evaluate the long time impacts (10 years) of roller chopping and buffelgrass seeding on grass yield, precipitation use efficiency and cover in a degraded site of the mentioned region. The treatments were: T0 = No roller chopping-seeding (Control) and T1= Roller chopping+buffelgrass seeding. Forage grass yield and precipitation use efficiency tended to be higher in T1 than in T0 during the evaluation period. Forage grass yield increment in T1 was highly associated to increment in total perennial grass cover (R2=91%), mainly due to buffelgrass cover (R2=76%). In T1, native perennial grass cover showed a negative lineal tendency in relation to years. Annual native grass, perennial native grass, total perennial grass and buffelgras covers followed a quadratic tendency related to years. Results of this study suggest that roller chopping and simultaneous buffelgrass seeding is, from a point of view of animal production, an efficient strategy for rapid restoration of grass cover and grazing capacity of degraded areas and that its effects maintains in the long time.
Keywords: Mechanical treatment; Buffelgrass; Forage yield; Grass cover; Precipitation use efficiency